Right of regret and objective good faith in Law 14.010/2020 (Research, Society and Development, 2020)
Among the measures taken by the Union to reduce the social impacts of COVID-19, in Brazil, there is the approval of Law 14.010/2020. One of the emergency rules of the aforementioned Law is the suspension, until October 30th, 2020, of decay deadlines, including the term for exercising the right of regret, within the article. 49, of the Consumer Protection Code, which allows the consumer to return unmotivated, within up to seven days, of a product purchased in person. Suspending this period until October 30th, the legislator ended up allowing, for example, the right of regret of a product purchased in July, to be exercised in early November. It turns out that the exercise of this right of regretting long after the purchase of the product, although it has not declined, under Law 14.010/2020, may generate a legitimate expectation that such right would no longer be exercised by the supplier. As a result, the supplier is supported by the rules pertaining to objective good faith, especially the loss of rights due to a retarded action (supressio), which prevents the late exercise of a certain right, when the inertia of the holder of that right has generated on the contrary the legitimate expectation that the right it would no longer be exercised. The present study, prepared through bibliographic researches, has the objective of demonstrating that the right of regret, even if not reached by decay, may have been achieved by supressio.